Design Model Environmentally Friendly Smokeless Household Waste Burning Stoves: Reality And Perceptions - Rabeea Mohammed Mansour Imleesha; Wasino Wasino; Rusdarti Rusdarti; Eko Handoyo; Meli Adriani Hotma Hasibuane (Prosiding Seminar Nasional Pascasarjana, 2021)
Abstract. Garbage is one of the most common environmental issues in the neighbourhoods. This issue is not limited to villages or towns; even industrialized countries are not immune to it. Several issues, such as the requirement for land for landfills, which has a severe influence on local inhabitants' health owing to smoke from open garbage burning, but whose onset is extremely dangerous to one's health. However, these findings have not been included in global illness burden estimations. Household air pollution is a key environmental risk factor that leads to more fatalities across the world. A garbage incinerator is equipment or machine for burning rubbish using combustion technology that is supposed to be ecologically beneficial and smoke-free in order to reduce air pollution. The objectives of this paper are 1) assess the forms of trash that are discarded in the home, 2) investigate the public understanding of environmental awareness in order to predict dangerous air pollution, and 3) develop an environmental care education model and create a smokeless waste burner stove.). In this mixed-methods design research, the researcher gives priority to main data collection (quantitative) and supporting data collection (qualitative).